2016
DOI: 10.1007/s11099-015-0164-8
|View full text |Cite
|
Sign up to set email alerts
|

Growth irradiance affects ureide accumulation and tolerance to photoinhibition in Eutrema salsugineum (Thellungiella salsuginea)

Abstract: Plants are able to acclimate to their growth light environments by utilizing a number of short-and long-term mechanisms. One strategy is to prevent accumulation of excess reactive oxygen species that can lead to photoinhibition of photosynthesis. Ureides, generated from purine degradation, have been proposed as antioxidants and involved in certain abiotic stress responses. Eutrema salsugineum (Thellungiella salsuginea) is an extremophilic plant known to exhibit a high degree of tolerance to a variety of abioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Allantoate and AT, urides, nitrogen storage, and transport compounds that recover nitrogen from purine rings showed substantial promise in plant stress tolerance. Endogenous accumulation of allantoate and AT in response to abiotic stress showed tolerance to a wide range of stresses [ 33 , 66 , 67 , 68 ]. In our experiment, both allantoate and endogenous AT decreased in UVC-stressed tomato plants ( Figure 5 A,B), which might interrupt the uride degradation in plants that is responsible for maintaining proper nitrogen homeostasis [ 69 ], resulting in decreased tomato plant protection against UVC stress ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Allantoate and AT, urides, nitrogen storage, and transport compounds that recover nitrogen from purine rings showed substantial promise in plant stress tolerance. Endogenous accumulation of allantoate and AT in response to abiotic stress showed tolerance to a wide range of stresses [ 33 , 66 , 67 , 68 ]. In our experiment, both allantoate and endogenous AT decreased in UVC-stressed tomato plants ( Figure 5 A,B), which might interrupt the uride degradation in plants that is responsible for maintaining proper nitrogen homeostasis [ 69 ], resulting in decreased tomato plant protection against UVC stress ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of photosynthetic acclimation in this process remains unknown for Eutrema , despite the fact transcript profiling and stress induced gene expression studies are almost always enriched by the differential expression of photosynthesis-related genes [ 29 , 30 , 33 , 34 , 41 , 42 , 43 , 44 ]. Previous studies have focused on the role of photosynthesis under salinity stress and photoinhibitory responses [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Plants were observed to acclimatise with HL and ML with an increase in specific leaf mass. This may happen because the ureide content increased by 2.5-fold in leaf tissues developed under varying irradiance conditions compared to non-irradiated ones [12]. Further, molecular studies demonstrated that the genes involved in both the synthesis and degradation of ureide were induced upon stress exertion.…”
Section: High Irradiancementioning
confidence: 99%